Factors Associated with Wound Complications after Open Femoral Artery Exposure for Elective Endovascular Abdominal Aortic Aneurysm Repair - Trinidad, Bradley (Int J Angiol, 2019)
We identified factors that would lead to wound complications after open femoral exposure for endovascular abdominal aortic aneurysm repair (oEVAR). Using the National Surgical Quality Improvement Program dataset (2005–2014), we examined the patients who underwent oEVAR. Patients were stratified on whether they developed postoperative wound complications. Comparisons were made between group with wound complications and those without and adjusted analyses performed to identify variables that independently increased the risk of wound complications. There were 14,868 patients in the study cohort and 2.6% (384 patients) developed wound complications after EVAR. Among those with wound complications, 94% (360 patients) of patients had superficial and deep surgical site infection. Patients who had wound complication were likely to be younger (72.6 vs. 73.7 years old ( p  = 0.02), functionally dependent (5.4 vs. 2.5%) ( p  < 0.05), smoker (3 vs. 2.4%, p =0.03), female (4 vs. 2.2%), with significantly higher body mass index (31 vs. 28), and more commonly had diabetes (4 vs. 2.4%, p  < 0.001) or renal failure (12 vs. 3%, p  < 0.001). Although perioperative survival was similar, patients who had wound complications had significantly longer hospital length of stay (LOS) (7.3 ± 12 vs. 3.4 ± 5 days, p  < 0.001). Up to 3% patients developed wound complications after open femoral exposure during EVAR with significantly higher LOS and therefore cost utilization.